UPAYA MEMPERTAHANKAN HUBUNGAN PERNIKAHAN BAGI CALON PENGANTIN DENGAN MENGGUNAKAN PENDEKATAN KONSEP STIFIn - Moh Rosil Fathony (SAMAWA, 2023)
Marriage is a relationship between a man and a woman. It is about developing solid communication skills as well as having sex. Remembering the high rate numbers of divorce in Indonesia, this thus serves as one of the supports. The purpose of this essay is to introduce the prospective bride and groom (CATIN) to the concept of STIFIn, found by Farid Poniman regarding the human brain hemispheres and includes: sensing, thinking, intuiting, feeling, and instinct. To help them more readily grasp the personality and lifestyle of their partner. This article is a review of the literature that uses a descriptive-analytic methodology. This research is beneficial for understanding one's own and other people's character, especially about bride and groom (CATIN) to obtain Sakinah, Mawaddah, and Warahmah. Keyword : Marriage, STIFIn, Bride